A serious game concept to enhance students' learning of statistics - Leão, Celina Pinto (2017)
In this ongoing work, the team intends to present a conceptual serious game as an educational tool to promote and demonstrate the applicability of statistical concepts in day-to-day life and in the decision-making process. The serious game will provide learning content in a game-based environment where students/players interact by applying knowledge in Statistics. There will be no right or wrong answers. Based on the students' answers and choices, the serious game, by a design mechanism, will lead them to different challenges until they reach the end. Students' answers must use concepts acquired in the classroom.